Trade-restrictive Measures under the WTO Framework in the Context of the COVID-19 Pandemic: The Example of China - Zhao, Yun; Lin, Lifei (American Journal of Trade and Policy, 2021)
The COVID-19 outbreak has led to shortages of critical medical equipment and supplies, exposing significant flaws in the global supply chain. A number of countries have adopted trade-restrictive measures in response to the domestic challenges posed by COVID-19. This paper analyzes whether the trade-restrictive measures adopted by various countries in response to COVID-19 are legitimate under the current WTO framework and how to reform multilateral rules on such measures to promote global equality in accessing essential supplies and coping with the de-globalization wave.With reference to China’s practice, the paper first examines the compatibility of the trade-restrictive measures induced by COVID-19 with the WTO framework, arguing that export restrictions are likely permissible under WTO rules as long as they are non-discriminatory, temporary, and necessary to achieve a certain degree of domestic protection. However, such measures may ultimately disrupt global supply chains and cause more harm, especially to vulnerable countries. The COVID-19 crisis may even lead to a post-pandemic wave of economic de-Sinicization and de-globalization. The paper further argues that it will be contrary to the globalization trend for countries to implement a policy of supply chain localization in the post-pandemic era. The paper concludes that the best solution for minimizing the losses induced by similar crises in the future is to refer back to the WTO framework and reform the rules pertaining to trade-restrictive measures to promote equitable access to key global supplies.
Keywords: covid-19; trade-restrictive measures; China’s response; WTO reform; GATT; global supply chain